2000
DOI: 10.1080/713654965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stress on growth, some blood variables and lipid oxidation in broilers exposed to high temperature at an early age

Abstract: 1. This study was conducted to determine metabolic and physiological responses of 2 commercial broiler strains, Hubbard (H) and Cobb (C), exposed to an ambient temperature of 38 degrees +/- 1 degree C for 2 h at 14 and 15 d of age. 2. Exposure to high temperature at an early age resulted in weight loss in strain C, which was not compensated for by 35 d of age but there was no weight loss in strain H. 3. Exposure of broilers to heat stress (38 degrees +/- 1 degree C) at 35 d of age resulted in an increase in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 0 publications
4
35
0
6
Order By: Relevance
“…This finding corroborates with Altan et al (2000) and Minka & Ayo (2008), who found an increase in H/L ratios when the birds were subjected to heat and transportation stress. Likewise, Nworgu et al (2007) and Minka & Ayo (2008) observed that the values of TLC and H/L ratio were stable when the broilers chickens were treated with anti-oxidant vitamins.…”
Section: H/l Ratiosupporting
confidence: 81%
“…This finding corroborates with Altan et al (2000) and Minka & Ayo (2008), who found an increase in H/L ratios when the birds were subjected to heat and transportation stress. Likewise, Nworgu et al (2007) and Minka & Ayo (2008) observed that the values of TLC and H/L ratio were stable when the broilers chickens were treated with anti-oxidant vitamins.…”
Section: H/l Ratiosupporting
confidence: 81%
“…It has also been found to be related to blood glucocorticoids levels (Davis et al, 2008). Therefore, H/L has been used to evaluate the welfare of chickens in stressful environments (Altan et al, 2000). In the present study, the H/L of C1C1 chickens presented a quadratic response (p<0.05) and C1C2 and C2C2 a cubic response (p<0.05) under heat stress (Figure 4d).…”
Section: Effect Of Hsp70 Genotypes On Hematological Responsementioning
confidence: 57%
“…Due to their lower tolerance to heat, the mortality rate of commercial broilers (46.0%) was extremely high, whereas it was only 2% in native chickens (2%). Reduced feed intake and growth performance due to heat stress has been documented in several reports (Mehta & Singari, 1999;Yuming et al, 1999;Altan et al, 2000;Oliveira et al, 2000;Temim et al, 2000;Deeb & Cahaner, 2001;Xin et al, 2002).…”
Section: Hsp70 Genotypes and Heat Tolerance Of Commercial And Native mentioning
confidence: 99%
See 1 more Smart Citation
“…Altan et al (2003) concluded that heat stress increased lipid peroxidation due to increased free radical generation, as indicated by the increased MDA concentration in broilers exposed to heat stress. According to Altan et al (2000), oxidative stress can be considered part of the broiler chicken response to heat exposure.…”
Section: Effects Of Heat Stress On Cell Dynamics Of Broiler Chicken Smentioning
confidence: 99%